Sexual objectification of women in alcoholic beverages print ads - Magracia, Mary Valorie Mangao
The use of women as sex objects has been the trend as marketing tool in alcoholic beverages through print advertisements as it is assumed to entice male consumers into buying the product. This undergraduate thesis is a descriptive research on the attitude of male consumers towards sexual objectification of women in print advertisements. Two theories serve as guide for this study: Standpoint Theory to explain that a person?s view on a particular issue is affected by his or her perception, and Objectification Theory that explains about women being portrayed as objects especially in advertisements. A survey of 300 males aged 18 and above, and exposed to alcoholic beverage print advertisements, shows majority of them enjoy looking at the women featured in these print ads. Therefore, male consumers have positive attitude towards sexual objectification of women in print ads of alcoholic beverages but this does not mean that they generalize women as sexual objects based on how these print ads portray them. The researchers recommend a correlational study on consumer?s attitude towards similar advertisements and their purchase decision as they see the need to challenge liquor companies and their advertisers in finding more creative marketing strategies to sell their products rather than sexually objectifying women in their ads.